EKSISTENSI BUDAYA BAHARI TRADISI PETIK LAUT DI MUNCAR BANYUWANGI - Eko Setiawan (IAIN Kediri, 2016)
Petik laut is an expression of fishermen community thanks in Muncar for treasure and safety given by God through nature, especially sea. Petik laut ritual is held annually on Muharram month or Syuro by the citizen lived on the coast. The focus of this article explains the existence of myth in petik laut ceremony in Muncar, ritual procession, and religious values existing in it. This article uses qualitative approach. In conclusion, the sequence agenda of petik laut combines Islamic doctrine and Osing custom. The intention and the purpose of various ceremony of the sea handout is commonly same namely asking to the God in order to fishermen get over sea yield in the next year and are avoided from disaster during fishing. Almost those fishermen community believe that sea has keeper (supernatural being). Therefore, in every sea ritual, they always give offerings given to supernatural being keeper the sea. Keywords: maritime custom, Petik Laut, Islam.